2015
DOI: 10.3389/fonc.2015.00086
|View full text |Cite
|
Sign up to set email alerts
|

Human Colon-Derived Soluble Factors Modulate Gut Microbiota Composition

Abstract: The commensal microbiota modulates immunological and metabolic aspects of the intestinal mucosa contributing to development of human gut diseases including inflammatory bowel disease. The host/microbiota interaction often referred to as a crosstalk, mainly focuses on the effect of the microbiota on the host neglecting effects that the host could elicit on the commensals. Colonic microenvironments from three human healthy controls (obtained from the proximal and distal colon, both in resting conditions and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…By monitoring the time course modi cations and evolution of the gut microbiota in this model, emerged that the effects of FMT were long-lasting but temporary, demonstrating the presence of a continuous bidirectional in uence between the microbiota and the gut, as previously postulated [35,36]. FMT DNBSinduced visceral hypersensitivity was evident already 24 h after the rst set of FMT, suggesting the presence of pain mediators in the supernatant obtained from the faeces, as supposed in other studies [17,37].…”
Section: Discussionsupporting
confidence: 73%
“…By monitoring the time course modi cations and evolution of the gut microbiota in this model, emerged that the effects of FMT were long-lasting but temporary, demonstrating the presence of a continuous bidirectional in uence between the microbiota and the gut, as previously postulated [35,36]. FMT DNBSinduced visceral hypersensitivity was evident already 24 h after the rst set of FMT, suggesting the presence of pain mediators in the supernatant obtained from the faeces, as supposed in other studies [17,37].…”
Section: Discussionsupporting
confidence: 73%
“…As observed in Sylvain et al (), the fish skin mucus and gut bacterial habitats show contrasting responses to variations of water physicochemical parameters. In the gut samples, factors other than hydrochemical parameters may influence the structure of the gut community, such as fish diet and immune response, both of these being known to modulate both microbiota structure and activity (Hevia et al, ; Sylvain & Derome, ). A recent study from Araújo, Ghelfi, and Val () has shown that gene expression patterns, including genes involved in the host immune response, differ depending on water colours in the Amazonian fish Triportheus albus .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other studies documenting the physiological response of fish to acid stress 30 show that fishes acclimate to the acid environment by modulating innate physiological parameters. Because innate physiological parameters are known to modulate both microbiota composition and activity 31 , the taxonomic structure of the endogenous microbiota on fish exposed to acidic pH will likewise be affected by the physiological response of its host. Perturbation of the taxonomic structure might elicit a disturbance of the bacterial functional repertory, impacting host immune defence.…”
mentioning
confidence: 99%